Trends of utilization of free maternal services implemented among postnatal women in sub-county hospitals of selected counties in Nyanza, Kenya - Nyaberi, Jackline Mosinya; Ochieng, Otieno G.; Justus, Osero O. S. (International Journal Of Community Medicine And Public Health, 2020)
Background: Low utilization and poor accessibility of hospital based maternal services in low and middle-income countries (LMIC) are evident and financial barriers is a major bottleneck. Globally, an estimated 600,000 maternal deaths occur yearly with over 90% of these deaths occurring in LMICs. In Kenya, maternal mortality is still relatively high with 362 maternal deaths per 100,000 live births. Gaps in the quality of maternal health services exist due to high costs, poor staffing and inaccessibility. However, Utilization of hospital based maternal services enhances skilled delivery and consequently reduces maternal and child mortalities and morbidities. The aim of this study was to establish the trends of utilization of free maternal services (FMS) before and after implementation in counties of Nyanza, Kenya. Methods: The study adopted an analytical cross-sectional study utilizing mixed methods of data collection. Secondary quantitative data on the rate of utilization between June 2011 and May 2015 was compared. Qualitative data was collected from key informants and focused group discussants. Purposive and simple random sampling were used to select target population. Data was analysed using both parametric and non-parametric statistical methods. Results: In maternal services utilization, Kisumu county recorded the highest 98.7%. Overall, in Nyanza, there was tremendous growth on trends of FMS utilization of 53.4% from 36.7% before implementation of FMS with cases of still births, maternal deaths and neonatal deaths. Conclusion: The upsurge of FMS utilization encouraged skilled birth attendance but also caused enormous constrains to health system and reduced the quality of FMS.